Interactive Web Geographic Information System Mapping Fire Prone Areas Using Dijkstra Algorithm: Pemetaan Sistem Informasi Geografis Berbasis Web Interaktif Lokasi Rawan Kebakaran Menggunakan Algoritma Dijkstra - Moningkey, Efraim R. S.; Ratu, Regina Gloria; Santa, Kristofel (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Fire disasters pose serious risks to public safety, material assets, and environmental sustainability, requiring rapid access to accurate spatial information. Specific Background: In Minahasa Regency, fire-prone area mapping and fire-fighting resource records are still managed manually, limiting information dissemination and slowing emergency response. Knowledge Gap: Existing practices lack an integrated web-based GIS that combines spatial visualization with shortest route analysis for operational fire management. Aims: This study aims to design and develop an interactive web-based Geographic Information System to map fire-prone areas, fire station locations, and water sources while providing shortest route recommendations using the Dijkstra Algorithm. Results: The system was developed using the Waterfall model with PHP, MySQL, and Leaflet.js, and black box testing confirmed that spatial data management, interactive visualization, administrative boundary filtering, and shortest route calculations operated as intended. Novelty: The research introduces the integration of fire-prone area mapping, fire-fighting resource management, and Dijkstra-based route analysis supported by OSRM within a single web GIS platform for Minahasa Regency. Implications: The developed system supports faster spatial information access and decision-making in fire management by providing route and water source recommendations through an interactive GIS interface. Highlights• Manual fire mapping processes were replaced by a centralized web-based GIS platform• Shortest route calculations were generated through integrated Dijkstra and OSRM services• Spatial visualization supported administrative filtering and emergency decision support KeywordsGeographic Information System; Fire Prone Areas; Dijkstra Algorithm; Spatial Mapping; Shortest Route